The Effect of Edmodo on Students’ Writing Skill in Recount Text - Adin Fauzi (The Faculty of Teacher Training and Education (FKIP), Universitas Sebelas Maret, Indonesia, 2017)
ABSTRACTThis study investigates the effect of Edmodo on students’ writing skill in recount text. The participants of the study were 9 students of Excellent Class of a Senior High School in Tulungagung, Indonesia. A pre-experimental study was employed as the research design to investigate the effectiveness of Edmodo in recount writing instruction. Following the research design, the students participated as both experimental and control groups. They did pretest at the beginning of this study, received treatment, and did posttest at the end of the study. The finding of the study revealed that the null hypothesis could be rejected. The convention to reject the null hypothesis is that when the p-value of the obtained statistics is less than 0.05. The finding showed that p-value was less than 0.05 (0.006<0.05). Referring to the data, there was enough evidence indicating that the null hypothesis could be rejected, and thus it could be concluded that using Edmodo was effective to teach recount text. This study attempts to contribute to the improvement of teaching writing by maximizing the use of ICT tools. Using Edmodo, both students and teachers can have a safe online environment to conduct more effective and sustainable teaching and learning process.